Eliminating postnatal HIV transmission in high incidence areas: need for complementary biomedical interventions - (:unkn) unknown (My University, 2021)
The rate of mother-to-child transmission (MTCT) of HIV from breastfeeding is increasing relative to other causes of MTCT. Early effective preconception and antenatal antiretroviral therapy (ART) reduces intrauterine and intrapartum MTCT, whereas maternal post-partum HIV acquisition, untreated maternal HIV, and suboptimal postnatal maternal ART adherence increase the risk of MTCT through breastfeeding. Although the absolute number of cases of MTCT acquired through breastfeeding is decreasing, the rate of decrease is less than the decrease in intrauterine and intrapartum MTCT. Unless current strategies are universally applied, they might not be sufficient to eliminate MTCT due to breastfeeding. Urgent action is needed to evaluate and implement additional preventive biomedical strategies in high HIV prevalence and incidence settings to eliminate MTCT from breastfeeding. Preventive strategies include: pre-exposure prophylaxis in breastfeeding women who have an increased risk of acquiring HIV; postnatal reinforcement strategies, such as maternal retesting for HIV, maternal care reinforcement, and prophylaxis in infants exposed to HIV via breastmilk; and active (vaccine) or passive immunoprophylaxis with long-acting broadly neutralising antibodies.
Keywords: African Research